Korupsi, Pidana Mati Dan Hak Azazi Manusia Dalam Perspektif Sistem Pidana - Said Abdullah (Jurnal LEX SPECIALIS, 2011)
Capital punishment as a kind of punishment for perpetrators of corruption as contained in Act No. 31 of 1999 jo. Act No. 20 of 2001 on combating corruption, in level of implementation is not very effective in efforts to eradicate corruption in Indonesia. That's because the Act contained in the sentencing weighting against the perpetrators of corruption, as contained in article 2, paragraph (2). So until now there has been no perpetrators of corruption was sentenced to death, but the imposition of capital punishment in the criminal justice system in Indonesia is still need to be maintained in the legislation, because corruption has to be transnational crime (national trans border crime) and recall complexity as well as negative effects, while from the aspect of human rights, capital punishment is very closely related because the punishment is an impact on human values are universal and fundamental rights of human beings who are entitled to feel the divine life. Key Note : Corruption, Criminal Dead And Human Rights